Faktor yang memengaruhi kunjungan penderita hipertensi di posbindu penyakit tidak menular (PTM) - Nurhasanah, Raden; Qomarania, Witri Zuama; Hosizah, Hosizah; Temesvari, Nauri Anggita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The results of the 2023 Indonesian Health Survey show that the prevalence of hypertension in Indonesia based on measurements of the population aged ≥18 years is 30.8%, but only 8.6% are diagnosed by doctors, while cases of hypertension at the Sukasari Health Center between 2020 and 2023 have doubled from 3.428 to 6.229 people. Integrated non-communicable disease development posts are one strategy in dealing with hypertension. On the other hand, hypertension sufferers who routinely visit integrated non-communicable disease development posts are still low at 45.7%. Purpose: To determine the factors that influence visits by hypertension sufferers to integrated non-communicable disease development posts. Method: An observational quantitative study using a cross-sectional method was conducted at the Sukasari Health Center, Sukasari Village, Tangerang District, Tangerang City, Banten in March-June 2024. The sampling technique used was total sampling and 155 samples were obtained. The research data collection was carried out by reviewing documents (secondary data) and the instrument used was a document review sheet to review data on visits to the integrated non-communicable disease development post. Results: This study shows that the most influential factors on visits by hypertension sufferers to the integrated non-communicable disease development post are primary education level (p-value = 0.007 OR = 11.140), secondary education (p-value = 0.026 OR = 7.266), prehypertension blood pressure (p-value = 0.041 OR = 2.698), and hypertension blood pressure level 2 (p-value = 0.045 OR = 0.369). Meanwhile, the variables that had no effect were gender (p-value=0.205), occupation (p-value=0.743), and comorbidity (p-value=0.497). Conclusion: The most influential factors on visits by hypertension sufferers to the integrated non-communicable disease development post were education level and blood pressure status. Suggestion: There should be efforts to increase the active role and support of health cadres and village officials in promoting the activities of the integrated non-communicable disease development post, through social media groups for residents in each region so that the community can diligently visit the integrated non-communicable disease development post. Keywords: Hypertension; Visit; Integrated Development Post; Non-Communicable Diseases. Pendahuluan: Hasil Survei Kesehatan Indonesia Tahun 2023, menunjukan bahwa prevalensi hipertensi di Indonesia berdasarkan hasil pengukuran pada penduduk umur ≥18 tahun sebesar 30.8%, namun hanya sebesar 8.6% yang terdiagnosis dokter, sedangkan kasus penyakit hipertensi di Puskesmas Sukasari antara tahun 2020 dan 2023 meningkat dua kali lipat dari 3.428 menjadi 6.229 jiwa. Posbindu PTM merupakan salah satu strategi dalam penanggulangan hipertensi. Di sisi lain, penderita hipertensi yang rutin berkunjung ke posbindu PTM masih rendah dengan persentase 45.7%. Tujuan: Untuk mengetahui faktor yang mempengaruhi kunjungan penderita hipertensi di posbindu penyakit tidak menular (PTM). Metode: Penelitian kuantitatif observasional menggunakan metode cross sectional yang dilaksanakan di Puskesmas Sukasari, Kelurahan Sukasari, Kecamatan Tangerang, Kota Tangerang, Banten pada Bulan Maret-Juni 2024. Teknik pengambilan sampel yang digunakan adalah total sampling dan didapatkan sebanyak 155 sampel. Pengumpulan data penelitian dilakukan dengan cara telaah dokumen (data sekunder) dan instrumen yang digunakan adalah lembar telaah dokumen untuk melakukan tinjauan data kunjungan posbindu PTM. Hasil: Penelitian ini menunjukkan bahwa faktor yang paling berpengaruh terhadap kunjungan penderita hipertensi di posbindu PTM adalah jenjang pendidikan dasar (p-value=0.007 OR=11.140), pendidikan menengah (p-value=0.026 OR=7.266), tekanan darah prehipertensi (p-value=0.041 OR=2.698), dan tekanan darah hipertensi tingkat 2 (p-value=0.045 OR=0.369). Sementara itu, variabel yang tidak ada pengaruh adalah jenis kelamin (p-value=0.205), pekerjaan (p-value=0.743), dan komorbiditas (p-value=0.497). Simpulan: Faktor yang paling berpengaruh terhadap kunjungan penderita hipertensi di posbindu PTM adalah jenjang pendidikan dan status tekanan darah. Saran: Adanya upaya untuk meningkatkan peran aktif dan dukungan kader kesehatan serta perangkat desa dalam mempromosikan kegiatan posbindu PTM, melalui grup media sosial warga pada tiap wilayah agar masyarakat dapat rajin berkunjung ke posbindu PTM. Kata Kunci: Hipertensi; Kunjungan; Penyakit Tidak Menular (PTM); Pos Pembinaan Terpadu (Posbindu).